Managing the Consequences of The Fragmentation of Religious Authority: Lessons Learned From Malaysia and Singapore - Fazlul Rahman (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2020)
Media infiltration in the Indonesian Muslim community has made the existence of religious authority increasingly fragmented. This fragmentation eventually gave birth to some serious consequences: loss of control to religious symbols, overlapping truth claims and relativization of religious authority. Several recent cases, starting from the mushrooming of Muslim celeb-clerics, cases of criminalization of ulama, bullying the figures of senior ulama on social media, to the politicization of ulama identities in elections, are clear tokens of the consequences. The question is how to manage those consequences of the fragmentation of religious authority? This paper discusses the problem based on a comparative analysis of the data collected during fieldwork in Malaysia and Singapore in 2018. The data was collected by interviewing imams, asatizah, and university professors in both countries as well as Indonesian professors and the grand imam of the Istiqlal Mosque as the complementary. Using the mediatization theory as its theoretical basis, this research found that there are several important arguments to deal with the consequences. As a concluding remark, this paper proposes a formula of maq??id -based media ethics as an alternative point of view of an ethical construction of Muslim society’s interaction with media.